Allocating unauthorised credit card payment losses: the credit card guidelines and consumer protection - Abd Razak, Adilah; Hood, Parker (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
Consumer with credit card payment facility faces the risk of unauthorised payment. Unauthorised payment occurs when a person initiated a credit card payment by using the consumer’s access device without his consent. It causes losses which are basically allocated between the issuer and the consumer according to the laws governing the bank-customer relationship. Apart from the old laws, the credit card payment system which uses new technology involves new transaction format and possesses some distinctive characteristics also requires new form of regulation. Considering the need, Bank Negara Malaysia had issued the Credit Card Guidelines 2003 (the CC Guidelines) to regulate the consumer-issuer relationship, including regulating the allocation of unauthorised payment losses. Because of the importance of the CC Guidelines’ loss allocation rules, this paper examines the rules to identify their impact on the consumer and also to give comments and suggest ideas for improvement. The findings revealed that the rules are ambiguous while at the same time failed to consider the impact of technological development on the payment systems. The ambiguities and weaknesses allow the issuer to allocate the losses by using the contract terms to the consumer’s prejudice. Therefore, it is recommended that the consumer should be aware of the contract terms that allocate fraudulent payment losses, in particular, terms that prescribe his duties and liabilities in relation to the losses. Finally, Bank Negara should revise the CC Guidelines to remedy the weaknesses.